PSEUDOANEURISMA ARTERI FEMORALIS - Mewengkang, Ester O V; Lefrandt, Reginald L (Jurnal Biomedik : JBM, 2012)
Abstract: Pseudoaneurysm is an accumulation of blood extravascularly in a space or cavity related to an artery, associated with disruptions of vessel layers. We reported a 51-year-old male with a pseuudoaneurysm of the left femoral artery. A lump in the left inguinal region occured due to a instrument wound during his fifth hemodialysis. The 6x5 cm-sized lump was hard, fixed, and painful in palpation, and had a bluish red center. A bruit was detected on auscultation. Diagnosis was based on the occurence of the lump in the inguinal region after the fifth hemodyalisis, a bruit on the lump, and a USG doppler examination that showed an aneurysm of the left femoral artery. The patient was operated on, and a pseudoaneurysm of the left femoral artery was found during the exploration. On day 36, the patient’s physical condition was improved and he was permitted to leave the hospital. From the pseudoaneurysm aspect, the prognosis of this patient was good, but in general the prognosis was dubia ad malam.Key words: pseudoaneurysm, femoral arteryAbstrak: Pseudoaneurisma atau aneurisma palsu adalah akumulasi darah ekstravaskuler dalam suatu rongga yang terhubung dengan arteri, disertai disrupsi lapisan pembuluh darah. Kami melaporkan kasus seorang laki-laki berusia 51 tahun dengan pseudoaneurisma arteri femoralis. Diagnosis ditegakkan berdasarkan gejala dan tanda klinis dimana ditemukan benjolan di lipat paha kiri yang timbul akibat tusukan pada saat menjalani hemodialis kelima, pemeriksaan fisik adanya bruit pada benjolan, dan USG doppler memperlihatkan adanya aneurisma arteri femoralis kiri. Pasien dilakukan pembedahan, dan pada saat eksplorasi ditemukan adanya pseudoaneurisma arteri femoralis kiri. Setelah perawatan hari ke-36, keadaan pasien membaik dan bisa dipulangkan. Prognosis pseudoaneurisma pada pasien ini baik, tetapi secara keseluruhan dubia ad malam.Kata kunci: pseudoaneurisma, ateri femoralis